1999
DOI: 10.1121/1.426687
|View full text |Cite
|
Sign up to set email alerts
|

Does music performance allude to locomotion? A model of final ritardandi derived from measurements of stopping runners

Abstract: This investigation explores the common assumption that music and motion are closely related by comparing the stopping of running and the termination of a piece of music. Video recordings were made of professional dancers' stopping from running under different deceleration conditions, and instant values of body velocity, step frequency, and step length were estimated. In decelerations that were highly rated for aesthetic quality by a panel of choreographers, the mean body velocity could be approximated by a squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
109
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 15 publications
(11 reference statements)
5
109
1
1
Order By: Relevance
“…Considerable contributions to our current knowledge on musical expression have been made by works following the paradigm of experimental psychology, in which controlled experiments are designed and executed, investigating a single aspect of performance, such as the timing of grace notes (Timmers et al 2002), or cyclic rhythms (Repp et al 2013). Local variations in tempo as a function of phrasing have also been explicitly addressed, using computational models (Todd 1992;Friberg and Sundberg 1999). Complementary to such approaches, often testing a specific hypothesis about a particular aspect of expression, data mining and machine learning paradigms set out to discover regularities in musical expression using data sets comprising musical performances (Widmer 2003;Ramirez and Hazan 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable contributions to our current knowledge on musical expression have been made by works following the paradigm of experimental psychology, in which controlled experiments are designed and executed, investigating a single aspect of performance, such as the timing of grace notes (Timmers et al 2002), or cyclic rhythms (Repp et al 2013). Local variations in tempo as a function of phrasing have also been explicitly addressed, using computational models (Todd 1992;Friberg and Sundberg 1999). Complementary to such approaches, often testing a specific hypothesis about a particular aspect of expression, data mining and machine learning paradigms set out to discover regularities in musical expression using data sets comprising musical performances (Widmer 2003;Ramirez and Hazan 2004).…”
Section: Introductionmentioning
confidence: 99%
“…shown to produce a good fit with a variety of empirical performance data (Friberg & Sundberg, 1999; but see also alternatives proposed by Repp [1992] and Feldman, Epstein, & Richards [1992], unrelated to the laws of physical motion; see Figure 1c). Friberg & Sundberg (1999) suggested that the final ritard alluded to human movement: the pattern of runners' deceleration.…”
mentioning
confidence: 99%
“…However, it is very difficult to specify-let alone validate-what is the nature of this longassumed relationship (Clarke, 2001;Honing, 2003). An important contribution to this topic is made by a family of computational theories, so-called kinematic models, that propose an explicit relation between the laws of physical motion (elementary mechanics) in the real world and expressive timing in music performance (Sundberg & Verillo, 1980;Kronman & Sundberg, 1987;Longuet-Higgins & Lisle, 1989;Feldman, Epstein, & Richards 1992;Todd, 1992;Epstein, 1994;Todd, 1995;Friberg & Sundberg, 1999). A large number of these theories focus on modeling the final ritard, the typical slowing down at the end of a music performance, especially in music from the Western Baroque and Romantic periods.…”
mentioning
confidence: 99%
See 2 more Smart Citations